Seismic Analysis of Building Using Modified Shear Wall: Enhancing Earthquake Resistance with Modified Shear Walls (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The shear wall plays important roles in the earthquake resistant buildings. The paper deals with the shear wall and modified shear wall for earthquake resistant building. The analysis of building has been done for shear wall and modified shear wall 12 storied building frame of by thickness 230mm,250mm 300mm it is observed that the resistance in vertical deflections decreases respectively. It is also observed that the reduction in base shear for 230mm,250mm 300mm respectively.